2008
DOI: 10.1007/s12028-008-9097-4
|View full text |Cite
|
Sign up to set email alerts
|

Placement of External Ventricular Drains and Intracranial Pressure Monitors by Neurointensivists

Abstract: Patients receiving ICP monitors had no complications. These complication rates are comparable to published rates, which suggest that placement of EVDs and ICP monitors by neurointensivists may be safe and effective. However, small sample size (n = 36) prohibits definitive safety and efficacy conclusions. For this reason, further research analyzing a larger patient sample is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 25 publications
2
35
1
1
Order By: Relevance
“…In one of the study it was demonstrated that hemorrhagic CSF -as a consequence of SAH or intraventricular hemorrhage (IVH) -occurred four times more frequently with a group of infected patients compared to the non-infected group [15]. Additionally the potential effect of SAH and IVH on the infection rate was mentioned in some of the later studies [7,[16][17][18][19]. Within our study the correlation between SAH and higher incidence of infections proved to be significant.…”
Section: Discussionsupporting
confidence: 63%
“…In one of the study it was demonstrated that hemorrhagic CSF -as a consequence of SAH or intraventricular hemorrhage (IVH) -occurred four times more frequently with a group of infected patients compared to the non-infected group [15]. Additionally the potential effect of SAH and IVH on the infection rate was mentioned in some of the later studies [7,[16][17][18][19]. Within our study the correlation between SAH and higher incidence of infections proved to be significant.…”
Section: Discussionsupporting
confidence: 63%
“…Hemorrhage rates after EVD placement varied widely from 1% to 33%. [22][23][24] Scholz et al 25 reported a hemorrhage rate of 14.8% in patients who underwent EVD placement after endovascular coil embolization of cerebral aneurysms under anticoagulation or antiplatelet therapy. The risk of ventriculostomy-related hemorrhage is higher in patients with SAH treated with stent-assisted coiling than in those with coiling without a stent.…”
Section: -12mentioning
confidence: 99%
“…3,5,6,8,10,12,[15][16][17][18][19][20][21] In particular, EVD-associated infections were found in 0% to 20% of patients in previous studies (Table 1), and the risk of surgery-associated hemorrhages or EVD device malplacements are often described. 3,5,6,10,12,[15][16][17][18][19][20][21] The highest reported complication rate of 33% shows the possible understatement of the catheter-associated complication risk. 15) The question still remains why this variety of perioperative complications is found and whether iatrogenic factors influence the surgical complication rate and thus the outcome.…”
Section: Introductionmentioning
confidence: 99%